(untitled) (CIPEEX, 2026)
Cannabis sativa L. is a plant historically used in different contexts, with Δ⁹-tetrahydrocannabinol (Δ⁹-THC) being its main psychoactive compound. Scientific interest in Δ⁹-THC has increased over the past decades due to its interaction with the endocannabinoid system, a complex regulator of physiological processes such as homeostasis, memory, emotional behavior, and pain perception. This study aimed to review the scientific literature on the pharmacological and toxicological effects of Δ⁹-THC, with an emphasis on its therapeutic role. Recent studies available in high-impact indexed databases were analyzed. The results indicate that Δ⁹-THC predominantly acts as a partial agonist of the CB1 receptor, modulating the release of neurotransmitters related to mood and motivation, in addition to presenting analgesic effects mediated by different molecular targets, including GPR55, TRPV1, and PPAR receptors. Despite the demonstrated therapeutic potential, limitations such as short duration of action and the possibility of adverse effects, especially anxiogenic responses, still restrict its clinical application. It is concluded that Δ⁹-THC represents an important starting point for understanding ECS physiology and for the development of safer and more effective cannabinoid-based drugs.